Canonical Correlation Analysis for Studying the Relationship Between the Basic Morphological and Some Soil Chemical Characteristics of Centaurea mucronifera DC. (Asteraceae) - CELIK, SEZGIN; YUCEL, ERSIN; MENDES, MEHMET; NILHAN TUG, G.; OZTURK, MUNIR (Asian Journal of Chemistry, 2010)
This aim of this study was to investigate the relationship between the basic morphological features and some soil chemical characteristics in order to enlighten the differentiation in the Centaurea mucronifera populations distributed at 16 different places under varying environmental conditions. For this purpose method of Canonical correlation analysis (CCA) was used. The results revealed that morphological features like length of terminal leaves (Y3), length of capitula (Y4), length of involucrum (Y5) and length of achen (Y6) are affected positively by N (X6) and Ca2+ (X7) in the soil but the length of plant (Y1), length of basal leaves (Y2) and length of pappus (Y7) are affected negatively.